O projeto de interiores do Escritório Empresarial em São Paulo: da informatização dos anos 1980 à globalização de 2000 - Fasanella, Ana Maria (2015)
This paper studies the business environments in the final two decades of the twentieth century. Three projects were selected in Sao Paulo, to describe the conditions and implementation of results, to the offices of companies that in some way were in evidence in the study time . The building were surveyed in its architecture - design and construction - in addition to interior design dedicated to each company . Projective questions, technology, market and human behavior at regional and global level, make the support to understand each of the three project, its characteristics and legacy. References researchers and specialized publications have been accessed to support and describe the research of this work .